LITERATURE REVIEW: PREGNANT WOMEN NUTRITION DURING A PANDEMIC - Rahayu, Kurnia; Rahmawati, Alfiah; Susiloningtyas (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
Pregnant women's nutrition is an important factor that must be met and taken into account during their pregnancy. Pregnant women and their fetuses benefit greatly from good nutrition during pregnancy. Nutritional intake throughout pregnancy is still something that should be considered for the womb's health. Pregnant women should get a good nutritional intake that includes four healthy five perfect foods in order to keep the mother and fetus immune during the pandemic. The purpose of this study is to look into the literature on pregnant women's nutrition. This study is a sort of literature review conducted using electronic databases such as PubMed and Google Schoolar. Each data-based publishing year is limited to the last ten years, beginning in 2011-2021. The publications obtained through the search include articles that include both international and national articles, and they will be then evaluated. The findings revealed that a pregnant woman during this pandemic requires additional nutrition since the mother must better maintain the immunity of the body and the fetus in her womb during this pandemic. If a pregnant woman normally requires 80.000 calories during pregnancy, the needs during the pandemic must be increased and presumed once more. During the pandemic, pregnant women should require some additional nutrients such as daily nutritional needs, supplements, iron, vitamin C, and macronutrient demands containing carbohydrates, proteins, and fats. To address the nutritional demands of pregnant women during a pandemic, pregnant women are recommended to eat breakfast every day, eat high-fiber foods, and enhance nutrient intake.